Technomadic Work: From Promotional Vision to WashTech's Opposition. (1st April 2008) - Michelle Rodino-Colocino,
Abstract : The purpose of this paper is to examine 'technomadic', or 'technomediated' mobile work at the levels of labour process and labour market. It investigates the promise of technomadic work at the level of the labour process, analyses the exploitation of technomadic work at the level of the labour market, and presents an instructive case study of the ways in which US workers are collectively struggling against such arrangements through the high-tech workers' union WashTech, the Washington Alliance of Technology Workers. The following analysis remedies gaps in the literature on technology and work by examining two overlooked phenomena: firstly the way in which the production of mobile labour markets contradicts the liberatory promise of technomadic labour processes; and secondly, workers' collective action against exploitation in the mobile, global labour market. By combining methods that interpret meanings within texts about labour processes with an empirical overview of trends regarding the labour market, this essay aims to contribute to the productive conversation between research in political economy and in cultural studies and to an understanding of divergence between the representations and experiences of technomadic work.